Candidate Species for Florida Aquaculture: Pinfish, Lagodon rhomboides - Cortney L. Ohs; Scott W. Grabe; Matthew A. DiMaggio (EDIS, 2010)
FA168, a 6-page illustrated fact sheet by Cortney L. Ohs, Scott W. Grabe, and Matthew A. DiMaggio, describes this marine baitfish of the Sparidae (porgy/sea bream) family which has potential for culture in the southeastern United States — general description, geographic distribution and habitat, natural history, culture techniques, broodstock nutrition, broodstock reproduction, hatchery, nursery, growout, disease, and market. Includes references. Published by the UF Program in Fisheries and Aquatic Sciences, School of Forest Resources and Conservation, May 2010.